A multisensory (visual, auditory, and olfactory) and teaching application concerning the history and production process of coffee - Guimarães, Marcelo de Paiva; Silva, Edna de Mello; Faria, Alessandro dos Santos; Argollo-Ferrão, André Munhoz de; Dias, Diego Roberto Colombo (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais Estendidos do XXIV Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2022.227649, 2022)
This project presents a multisensory (visual, auditory, and olfactory) and innovative teaching application concerning the history and production process of a beverage that influences pleasures, habits, interactions with family and friends, and work: coffee. The users are immersed in a virtual reality farm from the 19 th  century to experience harvesting, roasting, and coffee preparation, and to learn historical facts. The setup uses an olfactory display that allows the coffee aroma to be part of the user’s experience. This multisensory experience is innovative and astonishing, and it brings users closer to the traditional coffee production process. This project has been presented at the Major Novaes Museum, in Cruzeiro, SP, and has been demonstrated to be a very interesting experience to the users. They feel like in reality.